Whole-rock geochemistry and zircon O-Hf isotope compositions of ca. 2.35 Ga strongly peraluminous granites: Implications for increase in zircon δ18O values during the Paleoproterozoic. (1st September 2022) - Xie, Shi-Wen; Wang, Fang; Bucholz, Claire E.; Liu, Fu-Lai; Wang, Pei-Zhi; Bao, Ze-Min; Liu, Dun-Yi
Abstract: Zircon oxygen isotope ratios have been used to trace the incorporation of sedimentary rocks into magmas. The dramatic increase in maximum zircon δ 18 O values in the Paleoproterozoic observed in global databases coincides with changes in surface environments (e.g., the rise of subaerial and oxidative weathering), implying a connection between elevated zircon δ 18 O and these changes. Zircon δ 18 O between 2.5 and 2.2 Ga, however, is relatively under-constrained owing to limited available data in this age range. To augment data from this critical time period and understand potential causes for the elevated zircon δ 18 O values, we report U-Pb zircon ages and δ 18 O values of zircon, as well as, whole-rock major and trace element geochemistry of Paleoproterozoic strongly peraluminous granites (SPGs) from the southwestern margin of the Yangtze Block (China). Our geochronological data demonstrate that these SPGs crystallized at ∼2.35 Ga and that inherited zircon with ages of 2428–2721 Ma are present in these granites, indicating the source rocks of these granites were deposited, subsequently metamorphosed, and partially melted between 2.43 and 2.35 Ga. Synmagmatic zircon from samples dated in this study have εHf (t) values of −6.4 to −0.9 and high δ 18 O values of 7.6–9.9‰, elevated above the maximum value observed in Archean zircon (∼7‰). These granites can be divided into two groups based on whole-rock geochemistry. Both Group 1 and Group 2 granites were derived from a similar high δ 18 O, metapelitic source, but were generated by dehydration melting and hydrous melting, respectively. Our results demonstrate that the fine-grained sedimentary rocks from which the SPGs were derived had relatively high δ 18 O (as compared to older sedimentary rocks) by 2.43–2.35 Ga. The depositional time interval of the high-δ 18 O sedimentary sources for SPGs studied here coincides with the emergence of continental crust above sea level and the Great Oxidation Event. Supporting the findings of previous studies, the contemporaneity of our dataset with these changes in Earth's surface environments suggests that subaerial and potentially oxidative weathering contributed (at least partially) to the elevation of δ 18 O of fine-grained sedimentary rocks. Recycling of these high-δ 18 O sedimentary rocks into magmas contributed to the dramatic change in δ 18 O of magmatic zircon in the earliest Paleoproterozoic. In addition, although this study is focused on a single locality, our results suggest that the abrupt shift observed in global zircon δ 18 O data sets likely occurred by 2.35 Ga. Last, a literature compilation of zircon δ 18 O data from SPGs suggested that zircon δ 18 O values may have also experienced a stepwise increase in the Neoproterozoic to Phanerozoic from 12 to 14‰. The coincidence of these increases in zircon δ 18 O values with global oxygenation events suggests that atmospheric oxygenation may have contributed to the increase in δ 18 O of sedimentary rocks.